Government Policy Regarding Education Budget On The Posture Of The State Budget (APBN) In 2023 - Sulasmi, Emilda; Prasetia, Indra; Rahman, Arief Aulia (Universitas Pendidikan Ganesha, 2023)
Financing is one of the important instruments in achieving educational goals that must be managed effectively and efficiently and uphold the values of accountability. This must be used correctly, on target, and as needed. The purpose of this study is to analyze the National Education Budget policy that has been set by the government in the 2023 State Budget. The research method used is a descriptive method with a qualitative approach, the data collection techniques used are interviews, observations, and documentation studies. The overall data are then analyzed according to the phenomenological qualitative analysis model in a step: data managing, reading and memoing, describing, classifying, interpreting, and visualizing. The results showed that funding for education is a very important issue to improve the welfare of society and the quality of the young generation of a nation. The government in each country always strives to improve the quality of education of its people, especially through the allocation of adequate resources in the government budget, both central and regional. The National Education Budget in the 2023 State Budget posture has been set specifically for the education sector to reach IDR 612.2 trillion, consisting of the central government of IDR 237.1 trillion, transfers to regions of IDR 305.6 trillion, and financing of IDR 69.5 trillion. However, it should be noted that budget management is very vulnerable to misappropriation.